African music in Christian liturgy: the igbo experiment - Ekwueme, Lazarus (International Library of African Music, 1973)
One of the resulting effects of the Reformation in the Christian Church has been the making of worship more relevant to the masses of professed Christians. It has meant the employment of a vernacular which will be understood by the congregation, instead of a dead language comprehensible only to a few initiates who have spent years of apprenticeship in monasteries. It has also meant the use of tunes familiar to the worshippers, tunes in which they could join, whether in meek supplication, in holy adoration, or in hearty praise of the one who is, by faith, their Lord and Saviour. In an ever-evolving world, Christianity has continued to be a living faith by adapting to the changes of society through the ages. Contemporary Christianity continues to make changes to accommodate the philosophical attitudes of this nuclear age with its present- day ethics and 'new morality'. As different parts of the world are brought closer together by means of modern technology and communications, other religions exert a steadfast if subtle influence on the codes and dogma of Christianity, and even Papal authority gets diluted in the process of ecumenical interaction between the Roman Catholic Church and the Protestant denominations. Christianity, with its leadership, begins to view other religions such as Judaism and Islam with greater understanding and, in some cases, with unprecedented respect
Keywords: African Music